Sistem Hukum Pemberdayaan Masyarakat melalui Pengembangan Objek Wisata Air Terjun Masongsor di Desa Waleo Kecamatan Kema Kabupaten Minahasa Utara - Youla Olva Aguw; Deasy Soeikromo; Mercy M. M. Setlight (Bulletin of Community Engagement, 2026)
This study examines the legal system of community empowerment through the development of the natural tourism resources of Masongsor Waterfall in Waleo Village, Kema District, North Minahasa Regency, Indonesia. Masongsor Waterfall possesses significant ecotourism potential, featuring a height of approximately 100 meters and a scenic natural landscape that offers strong prospects for development as a regional tourist destination. Despite its potential, the development of this tourism area faces major challenges, particularly inadequate infrastructure, including limited road access extending approximately 9 kilometers to the site. This condition highlights the need for greater governmental support and intervention. The objectives of this study are: (1) to identify and analyze the legal regulations governing community empowerment through the development of the Masongsor Waterfall tourism resources in Waleo Village, Kema District, North Minahasa Regency; (2) to examine the implementation of legal provisions related to community empowerment in the development of the waterfall tourism area; and (3) to formulate a fair and welfare-oriented model of community empowerment through the sustainable development of Masongsor Waterfall’s natural tourism resources. The study is expected to contribute to the development of a legal framework for community empowerment in the management of natural tourism resources by promoting community participation, sustainability, and alignment with national development objectives.